(3JMdjd GdHjFI GdOGNdjI hGdNGQLjI (B- (3GSJQGJjLjGJ GdCYeGd CSQGQ GdJahb aj YGde JfGaSjs - (3eMeO(B, (3efjQs ((3GdEScfOQjI(B:s (3OGQ GdJYdje GdLGeYj(B,s, 2020)
(3JfGhd gPG GdcJGH ehVhY GdEOGQI GdGSJQGJjLjI h JMdjd GdHjFI GdOGNdjI hGdNGQLjI ddTQcI, HGdGVGaI Gdi GSJQGJjLjGJ GdCYeGd hCSQGQ GdJahb aj YGde JfGaSj(B.s
(3HHdjhZQGajG U(B.362s
Keywords: (3GdEOGQI GdESJQGJjLjIs